Photochemical and biophysical feedbacks of C3 and C4 Mediterranean halophytes to atmospheric CO2 enrichment confirmed by their stable isotope signatures - Duarte, B.
According the latest predictions, an increase of about two times in atmospheric CO2 concentrations, is expected to occur by the end of this century. In order to understand the effects of this atmospheric composition changes on two abundant Mediterranean halophytes (Halimione portulacoides and Spartina maritima), mesocosmos trials were performed simulating two atmospheric CO2 environments (380ppm and 760ppm of CO2 respectively). The two chosen halophyte species present different metabolic characteristics: H. portulacoides, is a C3 specie while S. maritima is a C4 species. Distinct feedbacks were obtained for each of the studied species. Stable Isotope discrimination showed that both species showed an enhancement of the Rubisco carboxylation capacity and photosynthetic efficiency mostly due to an increase in intracellular [CO2]. In H.portulacoides CO2 fertilization induced an enhancement of ETR and a decrease in non-photochemical quenching and in dissipated energy fluxes. On the other hand the C4 grass S.maritima, already at full capacity, showed no photosynthetic enhancement. In fact this highly productive grass presented lower photosynthetic efficiencies accompanied by increases in dissipated energy fluxes mostly due to reductions in energy flux associated with the transport of reducing power throughout the quinone pool. The accumulation of reducing power led to oxidative stress, and thus the photosynthetic ability of this grass was greatly reduced. Both these feedbacks to realistic future CO2 concentrations are important consideration for in future primary productivity models, indicating a possible reduced abundance of the pioneer S.maritima and an increased biomass spreading of the sediment stabilizer H.portulacoides, inevitably affecting the morphology and function of the salt marshes imposed by these atmospheric changes, both in terms of ecosystem functioning and loss of biodiversity.